The exploration of lanthanum based complexes oxides: preparation, characterization and gas sensing properties - Shingange, Katekani (University of the Free State, 2019)
A series of 1D metal oxide nanostructures based on Lanthanum (La) were synthesized through electrospinning followed by calcination. Firstly, the effect of La doping on ZnO was studied by introducing different concentrations (0, 0.06, 0.3, 1 and 2 wt%) of La and subjecting the obtained products to different annealing temperatures of 500, 700 and 900 °C. All La-doped ZnO sensors displayed enhanced sensor responses toward H2S as well as fast response/recovery times as compared to that of the pure ZnO based. Additionally, apart from the fact that these sensors displayed the highest responses, they also revealed relatively high selective responses to H2S. The sensor based on 2 wt% doping annealed at 900 °C displayed the highest H2S response as well as good repeatability, and stability. The H2S sensing performance of the ZnO nanofibres (NFs)was attributed to synergetic effects of a higher surface area, large number of intrinsic defects and the catalytic activity of La.Another study regarding LaCoO3and LaFeO3perovskites to investigate the influence of alternating the B-site cation on gas sensing revealed good acetone sensing at a low operating temperature of 120 °C with the LaFeO3NFs based sensor exhibiting high stable and selective response towards acetone with fast response and recovery time of 14 and 49 s.This high response was attributed to the high surface area and high density of oxygen related defects. A further, investigation on the annealing effect on LaCoO3NFs based sensors obtained after annealing at different temperatures of 550, 650, and 700 °Cwas iiconducted. Findings from field emission scanning electron microscope and high resolution transmission electron microscopedemonstrated that the synthesized LaCoO3 NFs consisted of a number of interconnected particles with average sizes of ~ 47, 58 and 77 nm, for 550, 650, and 700 °C annealing temperatures, respectively. Systematic gas sensing analysis revealed that the sensors based on LaCoO3NFs have substantial sensitivity to ethanol gas with the sensor obtained after annealing at 650 °Crevealing an outstanding response of 32.4 toward 40 ppm at a lower optimum operating temperature of 120 °C. While it exhibitedgood selectivity to ethanol gas as well as fast response and recovery speeds of 26 and 66 s, respectively. The enhanced sensing capability of the LaCoO3NFsbased sensor after annealing at650 °C stems from combined effects of the interparticle NFs structure, which provided high surfaceareaand porous channels. These allowed access to active sites as well as ease of gas diffusion and overlapping of the hole accumulation layers along the fiber direction producing continuous hole transfer channels. For the study of the effect of loading different concentration of Au on LaFeO3nanobelts (NBs),the gas sensing findings revealed that Au/LaFeO3NBsbased sensor with the Au concentration of 0.3 wt% displayed improved response of 125 to 40 ppm of acetone and rapid response and recovery times of 26 and 20s, respectively, at an optimal working temperature of 100 °C. Furthermore, all sensors demonstratedexcellent response and remarkable selectivity towards acetone. The gas sensing mechanism of the Au/LaFeO3sensors was explained in consideration of the catalytic activity of the Au nanoparticles, which served as direct adsorption sites for oxygen and acetone iiiLastly, a series of nanostructured La1−xCexCoO3perovskite oxides (x= 0-0.2), with NF morphology were prepared through the electrospinning method followed by annealing at 650 °C. The NF crystallite and particle size became smaller with an increasing Ce level, while the specific surface area increased linearly up to 25 m2/g. X-ray diffraction revealed that Ce segregated as CeO2 when the Ce addition level was x≥0.1. The NFs showed selectivity to ethanol with the pure LaCoO3showing its highest response of 32.4 at operating temperature of 120 °C,while La1−xCexCoO3(x= 0.2) revealed a high response of 83.4 at 100 °C. The La1−xCexCoO3 (x= 0.2) also displayed quick response and recovery times of 10 and 19s compared to the 240 and 286 s displayed by the pure LaCoO3. The improved sensing performance can be attributed to the increased surface area brought upon by the reduced crystallite and particle size, which ensured exposure of more active sites. Also, X-ray photoelectron spectroscopy revealed an increased amount of the surface oxygen, which played a role in facilitating the adsorption and oxidation processes of the ethanol. The sensing mechanisms involved between the nanostructures and the target gases are discussed in detail
Thesis (Ph.D. (Physics))--University of the Free State, 2019
Keywords: oxides; Lanthanum; metal oxides